Whole-genome resequencing reveals the genetic diversity, population structure and selection signatures in Chinese indigenous Kele pigs - Zhu, Yixuan; Wang, Xiaoyi; Lu, Ligang; Yang, Yongli; Chen, Qiang; Xu, Chengliang; Lai, Jinhua; Wang, Lixing; Wang, Shuyan; Li, Mingli; Lu, Shaoxiong (Frontiers in Veterinary Science, 2025)
IntroductionKele pig (KLP) is a valuable Chinese indigenous pig breed, renowned for its strong adaptability, high intramuscular fat content, and excellent meat quality. However, the genomic characteristics of KLPs are still unknown. This study aims to investigate the genetic diversity, population structure, and trait-related selection signatures of KLPs based on whole-genome resequencing.MethodsThe genomes of 30 KLPs were resequenced and analyzed alongside genomic data from 90 pigs of three commercial breeds, comprising 30 Duroc (DUPs), 30 Landrace (LRPs), and 30 Yorkshire pigs (YRPs). To evaluate their genetic diversity, we calculated the expected heterozygosity, observed heterozygosity, polymorphic marker ratio, minor allele frequency, nucleotide diversity (π), runs of homozygosity (ROH), and inbreeding coefficient (FROH). Meanwhile, a neighbor-joining tree, principal component analysis, ADMIXTURE analysis, linkage disequilibrium (LD) analysis, genetic distance and relationship matrices were constructed to analyze the population structure. In addition, selection signatures between KLPs and DUPs, LRPs, and YRPs were detected using fixation index (Fst) and π ratio methods.Results and DiscussionA total of 66,204,339 autosomal single nucleotide polymorphisms (SNPs) were detected in the 120 pigs, and 21,738,497 SNPs were retained for further analysis after filtering. The results showed that KLPs had higher genetic diversity, along with the smallest FROH value compared to DUPs, LRPs, and YRPs. Moreover, KLPs displayed a relatively unique genetic structure with a higher LD decay, and the majority of individuals within the KLPs exhibited distant genetic distances and relationships. Totals of 688 selected regions were identified, including 723 published QTLs. Within the selected regions, 192 candidate genes were annotated, and seven genes were found to be functionally involved in coat color (KIT), immune response (JAK2 and SOCS1), heart development (NTRK3 and SRF), muscle growth and development (VDR), and fat deposition (KDR). These findings will provide valuable insights for the future conservation, breeding, and utilization of KLPs.